Comparing performance of business and non-business students in entrepreneurship education / Sharifah Nurafizah Syed Annuar, Mydah Mylenda Eric and Ibianaflorinciliana Niane Anthony Aning. - Syed Annuar, Sharifah Nurafizah; Eric, Mydah Mylenda; Anthony Aning, Ibianaflorinciliana Niane (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
Entrepreneurship education has been discussed in numerous literature reviews as it plays integral roles for a country to move towards becoming a developed nation. Likewise, entrepreneurship education has been examined as one of the indicators in shaping entrepreneurial intention among university students and graduates. Given the significance of entrepreneurship education, recently, researchers have been discussing the right teaching method and devices in entrepreneurship education to educate non-business students. However, the distinction in performance in entrepreneurship education between business and non-business students are not completely investigated. Hence, this paper attempts to analyse and to compare performance between business students and non-business students in entrepreneurship education. ENT300 (Fundamental of Entrepreneurship) which is a compulsory course is used as a subject of this study. The results of students excel, pass and fail the course for seven sessions are recorded and analysed. The findings demonstrate that only one hypothesis was accepted and another two cannot be accepted. This paper adds to the entrepreneurship education literature and provides bits of knowledge to universities in better designing the curricular for entrepreneurship education.